Toxicological evaluation of submerged liquid culture from Phanerochaete chrysosporium mycelium on human blood cells: cytotoxicity, genotoxicity and oxidative damage - Fatime Geyikoglu; Salim Cerig; Murat Ozdal; Kubra Koc; Omer Faruk Algur; Gulsah Deniz Yildiz; Ozlem Gulmez (International Journal of Secondary Metabolite)
Mushrooms produce a variety of bioactive antioxidant secondary metabolites including ectins, polysaccharides, pigments, phenolic compounds, sterols and terpenes. Extracellular and intracellular compounds produced by submerged liquid fermentation are important industrially and economically. Phanerochaete chrysosporium (PC) is the model white-rot fungus that easy cultivation on lignocellulose-containing substrates. PC can be used as a bioprotein source. Aims of this study were to determine the in vitro antioxidant, cytotoxic and genotoxic effects of hot water extract obtained from PC on human peripheral blood monunuclear cells (hPBMCs). Cytotoxicity was determined by lactate dehydrogenase (LDH) leakeage assay and neutral red (NR). Total antioxidant capacity (TAC) and total oxidant status (TOS) were detected to determine the oxidative damage. Genotoxicity was characterized by micronuclei and chromosome aberrations assays for specify DNA damage. PC (5-75 µg/ml) significantly increased antioxidant capacity and these doses did not cause any significant alterations to cytotoxicity on hPBMCs. The elavated doses of PC (5-250 µg/ml) did not cause increase in genotoxic. Whereas, 250 and 500 µg/ml doses of PC statistically increased TOS levels, NR uptake, LDH release, CA/cell frequency and MN formation however decreased TAC levels. This study is the first time on cytotoxicity, genotoxicity and oxidative damage of PC on hPBMCs. In conclusion, the consumption of PC can be safe for humans, but it has also exposure period and dose-dependent effects on inducing oxidative damage and toxicity on hPBMCs.